1992
DOI: 10.1161/01.str.23.9.1325
|View full text |Cite
|
Sign up to set email alerts
|

Increases in cerebral blood flow in rat hippocampus after medial septal injection of naloxone.

Abstract: Background and Purpose:In a previous study, we occasionally found that the rat given naloxone in the preoptic region develops behavioral seizures. In view of knowledge that the forebrain including the medial septal nucleus provides cholinergic projections to the hippocampal formation, the present study examined the effects of naloxone injected into the medial septal nucleus on the local blood flow in the hippocampus.Methods: A polyurethane-coated platinum electrode with a l-mm bare tip for measurement of blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In return, this hypoperfusion could lead to the death of even more cholinergic neurons as the cholinergic neurons are energy-deprived. In rats, cholinergic inputs from the BF are responsible for increasing cerebral blood flow in the hippocampus (Nishimura et al, 1992;Sato et al, 2004); this can be impaired by limited NO production via a decrease of neuronal NO-synthase catalytic activity (Hartlage-Rübsamen and Schliebs, 2001). In humans, it has been shown that greater blood flow into the hippocampus is correlated with a better performance in spatial memory in older adults (Heo et al, 2010) and a greater hippocampal vascular reserve might be a protective factor against cognitive loss (Perosa et al, 2020).…”
Section: Alzheimer's Disease and The Basal Forebrain Cholinergic Systemmentioning
confidence: 99%
“…In return, this hypoperfusion could lead to the death of even more cholinergic neurons as the cholinergic neurons are energy-deprived. In rats, cholinergic inputs from the BF are responsible for increasing cerebral blood flow in the hippocampus (Nishimura et al, 1992;Sato et al, 2004); this can be impaired by limited NO production via a decrease of neuronal NO-synthase catalytic activity (Hartlage-Rübsamen and Schliebs, 2001). In humans, it has been shown that greater blood flow into the hippocampus is correlated with a better performance in spatial memory in older adults (Heo et al, 2010) and a greater hippocampal vascular reserve might be a protective factor against cognitive loss (Perosa et al, 2020).…”
Section: Alzheimer's Disease and The Basal Forebrain Cholinergic Systemmentioning
confidence: 99%
“…It has also been shown that among neurons located in the septum those projecting to the hippocampus have receptors for other substances such as monoamine [31,32], GABA [32][33][34][35], substance P [32] and opioid peptides [36,37]. All of these substances modified the activity of septo-hippocampal neurons.…”
Section: Apparatusmentioning
confidence: 99%